PEMBATALAN PENDAFTARAN MEREK PASSING OFF DAN KAITANNYA DENGAN ASAS UMUM PEMERINTAHAN YANG BAIK - Melati Widyatmanu Putri (2023)
In order to gain brand fame, another party willing to register a mark in bad faith using a well-known mark name without permission is called passing off. One of the cases that the researcher will discuss is the act of passing off the Starbucks brand owned by Starbucks Corporation against Starbucks owned by PT Sumatra Tobacco Trading Company. Starbucks Corporation was declared defeated at the first level because it could not prove its fame and won at the cassation level because it could prove its fame. and stated that there was an act of passing off. How was the basis used by the Supreme Court justices in granting the Starbucks Corporation's Cassation Application and how was the implementation of trademark registration which was proven to have passed off if it was related to the general principle of good governance because during the examination the existence of brand similarities had to be rejected. This research used an approach qualitative descriptive. The results of this study are that there is a first-instance judge's mistake in paying attention to international regulations that are bound by Indonesia in deciding cases of passing off Starbucks Corporation and not fulfilling some good general principle